Calibration concept and equipment drifting factors: its application in gas metering facilities - Mohsin, Rahmat; Nasri, Noor Shawal (1995)
A rapid development in gas industry has caused gradual increase of natural gas demand in the Malaysian market, which indirectly has drawn people’s attention to the price of natural gas and the accuracy gas measuring devices. The price of natural gas is a matter of supply and demand, while the determination of the accuracy of gas measuring devices is a matter of technology that is to be discussed in this paper. The aspect of calibration is a paramount factor in determining the accuracy of any measuring device. Some fundamental concept of calibration will be discussed in this paper to further enhance necessary understanding of gas metering calibration. A calibration concept plays an important role in any gas metering facilities due to a high quality measure of accuracy assurance in any flow monitoring device. This paper introduces some common terms and parameters which plays an important role in any calibration system. Some necessary understanding of metering facilities and its operation principles will also be presented. The basic calibration procedures for typical transducers and gas meters will also be highlighted.